Tailoring super-hydrophobic properties of electrochemical biosensor for early cancer detection. Issue 52 (5th August 2016) - Malara, Natalia; Gentile, Francesco; Ferrara, Lorenzo; Villani, Marco; Iannotta, Salvatore; Zappettini, Andrea; Di Fabrizio, Enzo; Trunzo, Valentina; Mollace, Vincenzo; Coppedé, Nicola
ABSTRACT: In this paper, we demonstrate an organic electrochemical transistor (OECT) based on the conductive polymer PEDOT:PSS for the analysis of the cell culture medium upon interaction with circulating cells isolated form peripheral blood sampling of health, sub-clinical and cancer patients. The device comprises arrays of super-hydrophobic micro-pillars in which a finite number of pillars incorporates nano-electrodes for site specific measurements of a solution. Due to its nano-scale architecture, the device realizes time and space resolved measurement of biological solution. Tumor metabolism could produce reactive species able to determine a different electronic behavior of correspondent microenviroment. On this basis, the device here presented the changes in the ESR signals was used to identify electronic changes occurring in the analysis of different type of microenvironment. Our results demonstrate that the device is able to register significative difference to differentiate healthy individuals form cancer patients, through an easy blood sampling. In conclusion, these preliminary data are suggestive of a novel test potentially useful to early identification of subjects at risk to development cancer disease.